Design of a nanoscale gold-coated photonic crystal fiber biosensor - Sarker, Sanchita; Vigneswaran, Dhasarathan; Studnička, Filip (Frontiers in Physics, 2023)
A simple two-layer refractive index sensor based on surface plasmon resonance has been proposed in this work, which evinces high sensitivity for detecting unknown analytes. This sensor design includes hexagonal- and octagonal-shaped air-hole rings, which have been introduced in the first and second layers, respectively. By performing this amalgamation of different types of air holes, this gold-coated plasmonic sensing scheme provides the broad sensing limit of the analyte, which is 1.32–1.40. The sensing performance has been examined by applying the finite element method, which is being used for modeling complex and irregular-shaped geometry. The wavelength interrogation method has demonstrated a maximal wavelength sensitivity of 9,000 nm/RIU (refractive index unit). The maximal amplitude sensitivity of 1902 RIU−1 has been exhibited in the y-polarized mode using the amplitude interrogation method. Moreover, the maximal sensor resolution of 1.11 × 10−5 RIU covers the entire sensing range. Furthermore, by adjusting the air-hole diameter, pitch, and depth of the gold layer coating, many more investigations have been demonstrated in this design. This highly sensitive sensor is very convincing to be used in many applications like chemical, biological, and also in physical sensing analyses.